1995
DOI: 10.1002/ana.410380411
|View full text |Cite
|
Sign up to set email alerts
|

Urinary myelin basic protein—like material as a correlate of the progression of multiple sclerosis

Abstract: In the multicenter, randomized, placebo-controlled trial of alternate-day injections of recombinant interferon beta-1b in relapsing-remitting multiple sclerosis (MS), urine specimens were collected periodically from all patients (n = 64) in two of the clinical test sites over the 2 years of the study. Urine specimens were also collected over two consecutive 24-hour periods from 43 patients from a third center. Urine samples were assayed for their content of myelin basic protein-like material (MBPLM), the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In addition, preexisting disability, the presence of a conduction block mediated by proinflammatory cytokines and clinically silent disease activity may confound the observed correlation between demyelination as assessed by the CSF concentration of MBP and the Kurtzke EDSS score.3' A comparison between CSF and MRI parameters and serial studies of CSF parameters were beyond the scope of the present study but are important aims of future studies of the MBP concentration in CSF as a disease activity marker in patients with MS. Unfortunately, no assays are available at present that allow measurements of MBP immunoreactivity in blood samples. A recent study suggests that increased serum concentrations of the astrocyte protein S-100 may correlate with disease activity in MS.32 There is only one previous study on the relation between the concentration of MBP in CSF and the CSF concentration of S-100 in MS and none on the relation to the concentration of S-100 in serum.5 It is possible to measure the concentration of MBP-like material in urine samples but this substance appears to be immunologically distinct from MBP-like material in CSF.33 In addition, high concentrations of MBP in urine may be a marker of progression rather than relapses in MS. 34 An association between CSF concentration of MBP and blood-brain barrier function as assessed by gadolinium enhanced MRI was previously reported.35…”
Section: Discussionmentioning
confidence: 80%
“…In addition, preexisting disability, the presence of a conduction block mediated by proinflammatory cytokines and clinically silent disease activity may confound the observed correlation between demyelination as assessed by the CSF concentration of MBP and the Kurtzke EDSS score.3' A comparison between CSF and MRI parameters and serial studies of CSF parameters were beyond the scope of the present study but are important aims of future studies of the MBP concentration in CSF as a disease activity marker in patients with MS. Unfortunately, no assays are available at present that allow measurements of MBP immunoreactivity in blood samples. A recent study suggests that increased serum concentrations of the astrocyte protein S-100 may correlate with disease activity in MS.32 There is only one previous study on the relation between the concentration of MBP in CSF and the CSF concentration of S-100 in MS and none on the relation to the concentration of S-100 in serum.5 It is possible to measure the concentration of MBP-like material in urine samples but this substance appears to be immunologically distinct from MBP-like material in CSF.33 In addition, high concentrations of MBP in urine may be a marker of progression rather than relapses in MS. 34 An association between CSF concentration of MBP and blood-brain barrier function as assessed by gadolinium enhanced MRI was previously reported.35…”
Section: Discussionmentioning
confidence: 80%
“…[20][21][22][23] However, despite differences identified at a group level, predictive value for an individual has been low. 24 Whereas it is possible to separate patients with MS from controls using techniques such as MRI, 12,13,25 or using a metabolomics-based approach on CSF samples, 26 to our knowledge no studies have been reported in which patients with RRMS and SPMS have been separated from each other on the basis of serum NMR.…”
Section: Discussion Usingmentioning
confidence: 99%
“…Studies from amyotrophic lateral sclerosis (ALS) also implicate excessive glutamate, passibly due to a defective glutamate transporter (48), though it remains to be seen whether any more direct link with calpain proteolysis will be made. With multiple sclerosis (MS), degradation of a preferred calpain substrate (myelin basic protein) is a key component in the pathology of the disease (74,80). though apparently no evidence exists to suggest a glutamate/calcium dysfunction and none yet directly implicates calpain proteolysis for the destruction of this key myelin protein.…”
Section: Other Chronic Neurodegenerative Diseasesmentioning
confidence: 99%